Multidimensional library for the improved identification of per- and polyfluoroalkyl substances (PFAS) - Kara M. Joseph; Anna K. Boatman; James N. Dodds; Kaylie I. Kirkwood-Donelson; Jack P. Ryan; Jian Zhang; Paul A. Thiessen; Evan E. Bolton; Alan Valdiviezo; Yelena Sapozhnikova; Ivan Rusyn; Emma L. Schymanski; et al. (Scientific Data)
Abstract As the occurrence of human diseases and conditions increase, questions continue to arise about their linkages to chemical exposure, especially for per-and polyfluoroalkyl substances (PFAS). Currently, many chemicals of concern have limited experimental information available for their use in analytical assessments. Here, we aim to increase this knowledge by providing the scientific community with multidimensional characteristics for 175 PFAS and their resulting 281 ion types. Using a platform coupling reversed-phase liquid chromatography (RPLC), electrospray ionization (ESI) or atmospheric pressure chemical ionization (APCI), drift tube ion mobility spectrometry (IMS), and mass spectrometry (MS), the retention times, collision cross section (CCS) values, and m/z ratios were determined for all analytes and assembled into an openly available multidimensional dataset. This information will provide the scientific community with essential characteristics to expand analytical assessments of PFAS and augment machine learning training sets for discovering new PFAS.